Clausewitz and the state - Paret, Peter (Oxford University Press, 1976)
Originally published in 1976, Clausewitz and the State presents a comprehensive analysis of one of the significant thinkers of modern Europe. Peter Paret combines social and military history and psychological interpretation with a study of Clausewitz's military theories and of his unduly neglected historical and political writing.